Morphometric variations of superior temporal sulcus (Annals of Medical Research, 2024)
Aim: This study focuses on the Superior Temporal Sulcus (STS), acrucial structure in the brain that delineates the anatomical boundary between the superior and medial temporal gyri. The STS is significant in social cognition, particularly in tasks involving cognitive empathy and perspective-taking. Understanding its anatomical relationship with superficial skull landmarks is vital for cranial surgery and surgical planning.Materials and Methods: The study involved an in-depth examination of the STS in sixteen adult human brains, totaling 32 hemispheres. The research included detailed measurements of sulcal lengths, assessments of sulcal depths, and observations of segment and branch variations within the STS.Results: The continuous pattern was observed in 28.6% (4 cases) of the left hemisphere and 71.4% (10 cases) in the right hemisphere. The interrupted pattern was identified in 55.6% (5 cases) of the left hemisphere and 44.4% (4 cases) in the right hemisphere. The temporal pole pattern was present in 77.8% (7 cases) of the left hemisphere and 22.2% (2 cases) in the right hemisphere. The number of segments in STS showed significant variation across these pattern types, with a p- value of 0.0001, indicating statistical significance.Conclusion: A comprehensive understanding of the STS's anatomy is essential for neurosurgeons as it serves as a critical guide in navigating cerebral pathologies.The anatomical and cadaveric studies substantially deepen our comprehension of the STS's structural variations, thereby enriching the field's knowledge base and potentially facilitating the refinement of neurosurgical planning processes.This research highlights the critical significance of the STS within clinical and neuroscientific frameworks, particularly its vital contribution to neurosurgical procedures.
Keywords: Superior temporal sulcus; Anatomy; Cadaveric study